Oorlogskorrespondensie van Jan Floris van der Wateren, 1900-1902 (Historia, 2021)
War correspondence of Jan Floris van der Wateren, 1900-1902. During the Anglo-Boer War (1899-1902) thousands of burghers from the Boer Republics were kept as prisoners of war by the British government. Jan Floris van der Wateren was separated for 32 months from his wife who was in Pretoria and during this time they corresponded regularly. The collection of 36 letters that he wrote to his wife provides interesting information about, amongst other things, his experiences on commando, the battles and the problems the burghers had to face, and Floris's life on St Helena as prisoner of war, until his return in October 1902. This collection provides a valuable source of information on a significant period in the history of the Afrikaner at the turn of the century.
Keywords: Van der Wateren J.F.; Letters; Anglo-Boer War 1899-1902; History; Prisoners of war